2014
DOI: 10.1002/acr.22212
|View full text |Cite
|
Sign up to set email alerts
|

Early Illness Features Associated With Mortality in the Juvenile Idiopathic Inflammatory Myopathies

Abstract: Objectives Because juvenile idiopathic inflammatory myopathies (JIIM) are potentially life-threatening systemic autoimmune diseases, we examined risk factors for JIIM mortality. Methods Mortality status was available for 405 patients (329 juvenile dermatomyositis [JDM], 30 juvenile polymyositis [JPM], 46 juvenile connective tissue disease–associated myositis [JCTM]) enrolled in nationwide protocols. Standardized mortality ratios (SMR) were calculated using United States population statistics. Cox regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 28 publications
2
56
1
Order By: Relevance
“…The clinical utility of myositis-specific autoantibodies in predicting prognosis in both adult and juvenile onset myositis has been noted by others (1,15). …”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The clinical utility of myositis-specific autoantibodies in predicting prognosis in both adult and juvenile onset myositis has been noted by others (1,15). …”
Section: Discussionmentioning
confidence: 68%
“…Juvenile dermatomyositis (JDM) is the most common clinicopathological form of JIIM. Additional phenotypes with higher morbidity and mortality are juvenile polymyositis (JPM), without the characteristic rashes of JDM, and juvenile connective tissue myositis (JCTM), in which patients meet the criteria for JIIM and at least one other autoimmune disease (1,2). The disease courses of JIIM can be distinguished into three types: monocyclic, polycyclic, and chronic (3,4).…”
mentioning
confidence: 99%
“…The common causes of death are progressive pulmonary disease, gastrointestinal problems (hemorrhage, perforation, vasculopathy), multisystem and idiopathic [7,29]. In spite of best efforts of the authors 2 of the JDM and 1 of the OM patients died (overall n = 3; 27%).…”
Section: Discussionmentioning
confidence: 91%
“…A large French national natural history study [62] of IBM revealed progressive functional disability but no overall increase in mortality. Predictors of mortality for polymyositis, dermatomyositis, and JDM have been determined and were found to be similar in different parts of the world and among phenotypes, with interstitial lung disease and the anti-synthetase autoantibodies among the risk factors predicting greater mortality [1**,37,67,82]. Classic epidemiologic investigations have been performed, deriving estimates of incidence and prevalence in national registries [3*,58], with documented increases in incidence over time for IBM in Australia and an increased prevalence of polymyositis and dermatomyositis in urban regions of Canada, for example [9,10*,97,129,138].…”
Section: Research Advances Through Myositis Registries and Biorepositmentioning
confidence: 99%
“…Clinical registries include national administrative efforts and health care systems’ tracking of medical utilization, costs, and outcomes, including such databases as the Social Security Death Index, from which mortality information may be gleaned [1**;2] or national health care registration systems that can be used to estimate disease prevalence in epidemiologic research [3*]. Registries may also include those that involve investigator-initiated research, with data collection that may include epidemiology, clinical features, outcomes, disease activity and damage assessments, and assessment of responses to therapies.…”
Section: Introductionmentioning
confidence: 99%